2014
DOI: 10.1186/1756-3305-7-170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multiple microsporidian infections and temperature stress on the heat shock protein 70 (hsp70) response of the amphipod Gammarus pulex

Abstract: BackgroundIncreasing temperatures can be a significant stressor for aquatic organisms. Amphipods are one of the most abundant and functionally important groups of freshwater macroinvertebrates. Therefore, we conducted a laboratory experiment with Gammarus pulex, naturally infected with microsporidians.MethodsIn each group, 42 gammarids were exposed to 15°C and 25°C for 24 h. Sex of gammarids was determined and microsporidian infections were detected by specific PCR. To quantify stress levels of the amphipods, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…505 and 515). The same microsporidians were previously detected in different amphipod species (Terry et al ., ; Krebes et al ., ; Grabner, Schertzinger & Sures, ; Grabner et al ., ; Weigand et al ., ), and can be considered amphipod specific. The only unique host–parasite association was found between the mayfly E. danica and the group D‐ Microsporidium .…”
Section: Discussionmentioning
confidence: 99%
“…505 and 515). The same microsporidians were previously detected in different amphipod species (Terry et al ., ; Krebes et al ., ; Grabner, Schertzinger & Sures, ; Grabner et al ., ; Weigand et al ., ), and can be considered amphipod specific. The only unique host–parasite association was found between the mayfly E. danica and the group D‐ Microsporidium .…”
Section: Discussionmentioning
confidence: 99%
“…Their transmission can be horizontal from one individual to another and/or vertical, directly from mother to offspring (Dunn & Smith, 2001). High prevalences and co-infection cases with up to three microsporidian species underline the importance of these parasites for amphipods (Haine et al, 2004;Grabner, Schertzinger & Sures, 2014;Grabner et al 2015). Due to intense proliferation of sporogonic stages microsporidians can modulate the host metabolism or its hormone homeostasis leading to feminization of male individuals (Bandi et al, 2001;MacNeil et al, 2003a;Smith, 2009).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%
“…Parasites are natural and ubiquitous parts of ecosystems and their role for ecosystem function and stability has been recognized in recent years (Marcogliese, 2005;Hudson, Dobson & Lafferty, 2006; Kuris et al, 2008). Nevertheless, parasites are often neglected in ecotoxicological research, although results of recent studies showed that they may influence the host response to pollution (Sures, 2004(Sures, , 2008aMarcogliese & Giamberini, 2013) and can impact the stress response of their host, especially on the biochemical level (Sures, Lutz & Kloas, 2006;Sures & Radszuweit, 2007;Frank et al, 2011Frank et al, , 2013Gismondi, Cossu-Leguille & Beisel, 2012a;Gismondi et al, 2012a,b;Filipović Marijić, Vardić Smrzlić & Raspor, 2013;Grabner, Schertzinger & Sures, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They are important in many cellular processes, including development, growth, protein folding, signal transduction and apoptosis. They play key roles in response to stress conditions such as thermal stress, parasite infections and heavymetal exposure, and protect organisms against environmentally induced cellular damage (Devaney, 2006;Grabner et al, 2014). Inhibitors of Hsp90 and Hsp70 were investigated as targets for treatment of cancer and parasitic diseases (Edkins and Blatch, 2012).…”
Section: Introductionmentioning
confidence: 99%